Comparative analysis of capillary threshold pressure measurement techniques: mercury intrusion porosimetry vs. innovative measuring tool for carbon storage - Soomro, Ahsan Nabi; Anioł, Łukasz; Kudasik, Mateusz; Dąbrowski, Karol; Nagy, Stanisław (Frontiers in Energy Research, 2025)
Threshold pressure is a critical parameter in evaluating the capillary sealing capacity of rocks, especially in reservoir and caprock studies related to CO2 storage and hydrocarbon recovery. In this research, we conducted a comparative analysis of two methods for measuring threshold pressure: the traditional mercury intrusion porosimetry (MIP), which operates under different fluid dynamics, and a new gas-water/brine system (e.g., CO2-water) using novel equipment. The new apparatus employs techniques to directly measure the threshold pressure by monitoring the displacement of water by gas, such as CO2, in core samples. This system is designed to more accurately replicate in-situ subsurface reservoir conditions by accounting for key parameters such as CO2-brine interfacial tension, and pressure. By directly measuring the point at which gas begins to displace water from rock pores, it provides a more realistic assessment of the threshold pressure for CO2 sequestration projects. For example, in the case of Sample 1, the direct measurement under a confining pressure of 15 MPa resulted in a threshold pressure of 0.4 MPa. In contrast, mercury intrusion data converted for CO2 drainage estimated the threshold pressure at only 0.1 MPa. Similarly, for Sample 2, the direct measurement yielded a threshold pressure of 0.24 MPa, while the MIP method indicated a significantly lower threshold of 0.05 MPa. These discrepancies underscore the limitations of mercury intrusion when applied to CO2-water/brine systems. Underestimation of threshold pressure can have significant consequences for the design and safety of CO2 storage projects, as this parameter is essential to assess the sealing efficiency of the caprocks and determine the storage capacity.